URGENSI BIMBINGAN DAN KONSELING (PENYULUHAN) ISLAM DALAM PENDIDIKAN - Enik Sartika (Syi’ar: Jurnal Ilmu Komunikasi, Penyuluhan dan Bimbingan Masyarakat Islam, 2019)
The existence of Islamic counseling held in educational institutions has a very vital urgency, because it is related to the Islamic moral development of students in the context of personality development. Through Islamic counseling, students are not only guided and advised on how to behave and behave, but also how students are aware of their role as a Muslim who has a need for the presence of God. So, students are guided to further increase worship for peace of mind and to be able to control emotions, because in mental tranquility it will bring clarity of mind so that it is not easily fragile when faced with a problem. The importance of Islamic Guidance and Counseling in education is an effort to help individuals to become human beings who develop in terms of education and form useful personalities in life who have various insights, views, choices, adjustments and skills according to themselves and their environment. So that the urgency of Islamic Guidance and Counseling is very important in order to achieve goals, development and optimization in the educational process.